Pengaruh Kompleksitas Operasional, Penggantian Manajemen, dan Ukran Perusahaan Terhadap Audit Repor Lag: (Studi pada Perusahaan Sektor Consumer Non-Cyclicals di Bursa Efek Indonesia Tahun 2021-2023) - Adrian Handa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial reports are made to provide information regarding the financial position, performance and changes in the financial position of a company and there are demands in reporting and compliance with the timeliness of submitting the company's financial reports. Consumer non-cyclical is a type of stock issued by companies whose business is not affected by the seasons or economic cycles in a country. The purpose of this study is to test and analyze the effect of operational complexity, management replacement and company size on audit report lag. The data used in this study are secondary data accessed through the website www.idx.co.id with 65 research samples. The results of this study indicate that operational complexity, management replacement, and company size have an effect on audit report lag.